Honey, Baby, Sweetheart - Caletti, Deb. (New York : Simon & Schuster Books for Young Readers, 2004)
In the summer of her junior year, sixteen-year-old Ruby McQueen and her mother, both nursing broken hearts, set out on a journey to reunite an elderly woman with her long -lost love and in the process learn many things about "the real ties that bind" people to one another.
900
Accelerated Reader AR
Keywords: Interpersonal relations -- Juvenile fiction; Self-perception -- Juvenile fiction; Old age -- Juvenile fiction; Love stories